Abstract 263: Cocaine Use and Acute Ischemic Stroke: Determining TOAST Etiology & Infarct Locations - Sachin Kothari; Harsh Desai; Anit Behera; Rami Z. Morsi; Julian Carrion‐Penagos; Matthew Smith; Elisheva Coleman; Tareq Kass‐Hout; James Brorson; Shyam Prabhakaran; Scott J. Mendelson (Stroke: Vascular and Interventional Neurology)
Introduction Cocaine‐induced vasospasm of small vessels has long been proposed as a mechanism for ischemic stroke (1). However, there are limited studies to date that have classified cocaine‐related ischemic strokes under a subtype of the Trial of ORG 10127 in Acute Stroke Treatment (TOAST) criteria. This study aims to describe cocaine‐related ischemic strokes by TOAST criteria, treatment, and clinical outcome. Methods A retrospective review was performed to identify patients with acute ischemic stroke and a positive cocaine urine toxicology screen at our stroke center from June 2020 – May 2022. Baseline demographics, urine toxicology, National Institute of Health Stroke Scale (NIHSS) scores, neuroimaging, TOAST criteria, location of stroke, home medications, comorbidities, medical management, and in‐patient outcomes were collected. Data analysis was conducted on IBM SPSS Version 28. Results A total of 74 patients were identified to have a positive cocaine status on admission with a diagnosis of new strokes. The mean age was found to be age 60.8 years old with a majority male population at 73.0% (54/74). Seventy‐eight percent (58/74) were found to be cocaine positive on admission with the remaining endorsing a history of cocaine use. The most common category under the TOAST criteria was large artery atherosclerosis 39.2% (29/74). Among the cocaine‐positive cohort, 10.8% (8/74) of patients received thrombolytics. Most patients had intracranial atherosclerotic disease (46/74, 62.2%) on imaging and in the area of the stroke (41/74, 55.4%). Overall mortality was low (72/74, 97.3%) and modified Rankin score (mRS) at discharge was less than 3 for 59.5% (44/74) of patients. Conclusion Our data suggests that although cocaine may contribute to small vessel disease, cocaine‐related ischemic strokes may have a higher association with large artery atherosclerosis. This study highlights the importance of future larger studies to investigate atherosclerosis as a contributor to cocaine‐induced ischemic strokes.